Equine colic due to gastric impaction in a thoroughbred mare - Choez A., Katherine (2017)
This paper describes a case of colic that ended in death due to gastric impaction occurred to a mare of 12 years of age. This case was triggered by the accidental and voracious consumption of concentrate feed intended for alpacas during a failure of supervision by staff. The clinical picture was characterized by severe depression, severe abdominal pain, lateral decubitus and inability to rise, with a rapid course and poor prognosis which turned fatal. Gross lesions included severe stomach distension, which was impacted with plenty content partially digested, fibrous and dry, with mucosal ulcerations and presence of serous exudate in the abdominal cavity.